Characterization of a supercharger as boosting & turbo-expansion device in sequential multi-stage systems. (15th March 2017) - Romagnoli, A.; Vorraro, G.; Rajoo, S.; Copeland, C.; Martinez-Botas, R.
Highlights: Experimental and numerical activities on an Eaton supercharger are reported. The supercharger was tested to investigate multistage boosting systems. Heat loss assessment and its influence on the supercharger efficiency was carried out. Experimental results were compared with a validated 1-D supercharger model. Assessment of the supercharger potential operating as an expander device. Abstract: This paper proposes a detailed performance analysis and experimental characterization of a high-pressure supercharger in a multi-stage boosting system (turbo-super arrangement). Infact, besides the technical challenges associated with achieving adequate tuning, interoperability and driveability of multi-stage boosting systems, another challenge lies in their performance prediction during engine design. Indeed, performance maps of single boosting systems are usually provided by manufacturers and used as look-up tables in 1-D engine models. Tests are usually conducted in a standalone mode, with no information provided on the behaviour and performance of the combination of more than one boosting device. The supercharger was tested with varying inlet pressures and temperatures matching on-engine operating conditions and the results were then used to assess the effectiveness of 1-D engine models performance prediction when dealing with multi-stage boosting systems. An assessment on heat transfer in superchargers was also carried out together with the analysis on the nature of non-dimensional performance maps when dealing with a pressurized inlet. Finally, the analysis also looked into the opportunity to use the superchargers as expanders ('expansion mode') in order to cool the air charge entering the engine. The results showed that there is discrepancy between the efficiency values computed by 1-D engine models and those obtained experimentally under pressurized/heated inlet air conditions; the correction of the efficiency maps for heat transfer plays a significant role in the final measured efficiency and the correction of the maps for varying inlet temperatures must be carried out in order to avoid incurring in apparent efficiencies greater than unity. The experiments on the supercharger in 'expansion mode' showed that low isentropic efficiencies can be achieved; despite this, 1-D engine simulations showed that it is possible to achieve savings of a few percentage points in Brake Specific Fuel Consumption when the supercharger is used to recover some throttling energy by expanding the close-to-ambient pressure to the required intake pressure.